Controlled Electron‐Induced Fabrication of Metallic Nanostructures on 1 nm Thick Membranes. Issue 45 (20th October 2020) - Preischl, Christian; Le, Linh Hoang; Bilgilisoy, Elif; Vollnhals, Florian; Gölzhäuser, Armin; Marbach, Hubertus
Abstract: Functional hybrids comprising metallic nanostructures connected and protected by nonmetallic 2D materials are envisioned as miniaturized components for applications in optics, electronics, and magnetics. A promising strategy to build such elements is the direct writing of metallic nanostructures by focused electron beam induced processing (FEBIP) onto insulating 2D materials. Carbon nanomembranes (CNMs), produced via electron‐induced crosslinking of self‐assembled monolayers (SAMs), are ultrathin and flexible films; their thickness as well as their mechanical and electrical properties are determined by the specific choice of self‐assembling molecules. In this work, functionalized CNMs are produced via electron beam induced deposition of Fe(CO)5 onto terphenylthiol SAMs. Clean iron nanostructures of arbitrary size and shape are deposited on the SAMs, and the SAMs are then crosslinked into CNMs. The functionalized CNMs are then transferred onto either solid substrates or onto grids to obtain freestanding metal/CNM hybrid structures. Iron nanostructures with predefined shapes on top of 1 nm thin freestanding CNMs are realized; they stay intact during the fabrication procedures and remain mechanically stable. Combining the ease and versatility of SAMs with the flexibility of FEBIP thus leads to a route for the fabrication of functional hybrid nanostructures. Abstract : Hybrids comprising conducting nanostructures connected and protected by ultrathin, nonconducting carbon films are fabricated by direct write focused electron beam induced processing of iron precursors onto self‐assembled monolayers. Subsequent crosslinking into carbon nanomembranes yields freestanding metal/carbon hybrids with predefined shapes leading to a new route for the fabrication of flexible metallic nanostructures.